Abrupt Climate Change: Time is tight - Jan-Erik , (Archives of Business Research, 2019)
The new theme of abrupt climate change (“Hawking tipping point”) must be taken up by global coordination – the UNFCCC, IPCC and the G20. The only policy response is to reinforce the COP21 project, and start managing its quick implementation of decarbonisation. A more decisive climate change policy – no coal or charcoal, solar power parks, and possibly carbon capture – may not guarantee the goal of + 2 degrees Celsius, but it may help avoid climate chaos. Only global coordination can break through the resistance of markets in the rich countries and governments in the Third World together with vibrant civil society. The large COP21 Secretariat must become a management agency for rapid decarbonisation with support from other global bodies (WB, IMF) and the G20.